Incidence of melanoma in organ transplant recipients and assessment of their survival and prognosis - Imko-Walczuk, Beata; Ankudowicz, Anna; Jaśkiewicz, Janusz; Dębska-Ślizień, Alicja; Rutkowski, Bolesław (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Increased risk of skin cancers in patients after organ transplantation is well known and documented. Much less is known about the incidence of melanoma and the prognosis of patients with this tumour. Melanoma patients after organ transplantation should be considered in three clinical aspects: tumour arising in patients after organ transplantation, as recurrent outbreaks of treatment prior to transplantation or melanoma transferred from a donor. Objective . The aim of this study was to determine the risk of melanoma and to reach the data for survival and prognosis in patients with this tumour after organ transplantation. Material and methods . Data concerning the incidence of melanoma in patients after transplantation were collected and analysed at the University of Oxford, Oxford Transplant Centre and Dermatology Department. The analysis was performed for 1958 patients who underwent 2342 organ transplantations. In order to evaluate the survival and prognosis of organ transplant recipients with melanoma, data from 14 European centres who are members of SCOPE were analysed. Results . In the study at the University of Oxford, 14 cases of invasive melanoma in 12 patients after renal transplantation were diagnosed. Cumulative melanoma risk factor equal to 8.4 per 10 000 transplant-years and 5-fold increased incidence of melanoma in the Oxford population of organ transplant recipients were established. In European centres, members of the SCOPE association, 89 cases of melanoma after organ transplantation were diagnosed. The study demonstrated that melanomas in T1 and T2 stages developing after transplantation have a similar prognosis when compared to the general population, while the prognosis of patients with T3 and T4 melanoma was significantly worse. Conclusions . Due to worse prognosis of organ recipients with melanoma it is extremely important to detect it at a very early stage, giving the chance of complete recovery after standard surgical treatment.